Anesthesic Management for Escobar Syndrome: Case Report - Ayse Hande Arpaci; Fusun Bozkirli; Onur Konuk (Case Reports in Medicine)
Escobar syndrome is a rare autosomal recessive disorder which is characterized by growth retardation, axillary, antecubital, popliteal digital, and intercrural joint flexion contracture, pterygium in the eyes, cleft palate, decreased lung capacity, genital abnormalities, and spinal deformity. In this case, we presented the anesthesic management of a 2-year-old child undergoing frontal sling operation for ptosis and amblyopia etiology exploration.